S26 Untargeted sputum proteomics reveals anti-inflammatory effects of CFTR modulation. (11th November 2022) - Maher, RE; Barrett, E; Barry, PJ; Emmott, E; Jones, AM; McNamara, PS; Smith, JA; Tewksbury, D; Lord, RW
Abstract : Background: Global proteomics methodologies identifies disease pathways and protein biomarkers with translational potential by capturing the proteome, an entire set of proteins within biological samples. These techniques were applied to a cystic fibrosis (CF) cohort commencing the cystic fibrosis conductance regulator (CFTR) modulator elexacaftor/tezacaftor/ivacaftor (ETI), which partially restores CFTR function with dramatic improvements in lung function. The sputum proteome differs between CF and healthy controls with increased neutrophilic inflammation and differences in protease/anti-protease and oxidant/antioxidant states, and differences become more pronounced with lung disease severity. We hypothesised that ETI would shift the proteome, so it more closely resembled healthy controls. Methods: Spontaneous sputa were collected pre- and post- therapy (n=25) and compared to stored healthy control induced samples (n=15). Samples were analysed by liquid chromatography mass spectrometry. Run alignment and peak picking was by Progenesis QI and proteins identified from the UniProt database. Clinical data was from medical records. Results: Mean absolute increase in FEV1 was 15% (SD 7.8). Obvious sputum proteome changes were seen with ETI using principal component analysis and hierarchical clustering, with the proteome post-therapy more closely resembling healthy controls. From the 441 proteins identified in sputum samples (≥2 unique peptides and false discovery rate <1%) 115 changed significantly (adjusted p value <0.05): 25 decreased and 90 increased post-therapy. Using Gene Ontology these changes appear driven by reductions in neutrophil activity and counterregulatory responses. The changes in proteome showed weak correlation with change in FEV1% (R 2 =0.32, p-value = 0.0029) but not BMI (R 2 =0.037, p-value = ns). Most subjects did not achieve a 'normal' proteome even after therapy. Conclusions: Reduction in neutrophilic airway inflammation may contribute to the clinical response seen with CFTR modulation. Proteome changes are largely independent of lung function and most CF subjects do not achieve the protein levels observed in healthy controls. This suggests a role for inflammatory biomarkers to complement existing clinical measures to assess CFTR modulation response or more broadly in clinical care. Our data also suggests a possible role for anti-inflammatory therapies for patients ineligible but also those receiving ETI as evidenced by the lack of full resolution of neutrophilic inflammation.